Promoting project progression: Creating a pipeline for industrial decarbonisation in Scotland - Durusut, Emrah; Assem, Dina; Simon, Richard; Garcia-Calvo Conde, Enrique (Element Energy, 2020)
Scotland's commitment to achieving net-zero greenhouse gas emissions by 2045, will require the decarbonisation of all sectors, including industry. The Scottish Government is working to create the right conditions to support investment in industrial decarbonisation. Such conditions require the reduction of industrial emissions while maintaining a competitive and healthy industrial sector, where decarbonisation is not achieved at the expense of loss of output, jobs or skills. This research aims to establish and develop a greater understanding of industrial decarbonisation projects in Scottish EIIs, to catalogue the pipeline of such projects, and identify overarching decarbonisation themes. It also aims to assess how projects are likely to develop over a 10-year timescale. Barriers, enablers and gaps in industrial decarbonisation in the listed themes are identified through understanding how decarbonisation technologies are adopted in Scotland, based on stakeholder engagement. The final objective is to inform the most likely development pathways and gauge the influence of external factors on optimal project sequencing.
Keywords: industrial decarbonisation; Climate Change; Scotland